The Evolution of the World’s Most Valuable Brands in the Period 2018-2023 - Sorin-George Toma (Ovidius University Annals: Economic Sciences Series, 2023)
The competition between enterprises has become more fiercely as they have the possibility to easily move across national boundaries to exploit opportunities in other countries or markets. The turbulent market environment imposes enterprises, irrespective of their size, industry and geographical region, to permanently adapt to its everchanging conditions. This is why they have tried to identify and implement various techniques and methods in their activities and processes in order to attain high levels of competitiveness. One of them is branding, a powerful marketing tool and an important aspect of any business. The paper aims to briefly define the brand concept and present the evolution of ten world’s most valuable brands in the period 2018-2023. In this respect, the author used a qualitative research method. The results of the paper concludes that the American brands have dominated the hierarchy. Amazon and Apple were the two main competitors for the global supremacy.